Letter: multivariate clinical model for eosinophilic oesophagitis – is this generalisable to a general population? Authors' reply. Issue 6 (17th February 2017) - von Arnim, U.; Röhl, F. W.; Miehlke, S.; Jechorek, D.; Reinhold, D.; Wex, T.; Malfertheiner, P.
Abstract : Linked Content This article is linked to Von Arnim and Rohl et al and Chitsaz papers. To view these articles visithttps://doi.org/10.1111/apt.13869 andhttps://doi.org/10.1111/apt.13919 .